The inclusion and assessment of climate related and environmental related risks in the banking industry: the UniCredit case. - Gioia, Giovanni Luigi (LUISS Guido Carli, 2021)
The nexus between climate-related risks and financial risk. From nuclear to climate apocalypse. The turning point: Paris agreement and UN 2030 agenda for sustainable development. The VUCA world. The European Union as pioneer of ESG revolution. Climate-related risks in the banking sector. The EBA framework of ESG risk for financial institutions. The principles for responsible banking. Environmental-related risk assessment. The mispricing of the environmental-related risks. The environmental-related disclosure as a risk mitigation tool. How do UniCredit assess, monitor and mitigate climaterelated risks. UniCredit’s financial risk management framework. Comparison with KPMG benchmark.

A critical analysis of the effect of the moratorium on property owners - Beekarun, Yasthil (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: Business rescue

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Cryptocurrencies in an insolvent estate - Du Plessis, Shandi (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Smart contracts : the Fourth Industrial Revolution and private international law - Dwamena, Elizabeth (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The impact of Covid-19 on labour law protection for Uber drivers - Gxabu, Mampho Aphelele (University of Johannesburg, 2021)
On 15 March 2020 the President of the Republic of South Africa announced a nationwide lockdown. The unpredicted pandemic dictated that extraordinary measures be put in place, which resulted in the country coming to a total standstill. Consequently, there was an alarming decline in economic activities and therefore government had to introduce measures to mitigate the impact of COVID-19 on employers and workers.

The tax implications of intellectual property: an overview of the development of the law pertaining to deductions - Khan, Ilhaam (University of KwaZulu-Natal, 2021)
No abstract available.

The tripartite free trade area: towards a comprehensive African economic community with a particular focus on SADC - Mabinza, Siqhamo (University of KwaZulu-Natal, 2021)
No abstract available.
Keywords: Africa; GATT; Multilateral trading systems; Regional Trade Agreements (RTAs); SADC; Southern African Development Community; WTO

The principle of party autonomy in the HAGUE principles on choice of law in International Commercial Contracts : lessons for Chinese, Russian and South African Private International Law - Manganye, Makhanani Annastesia (University of Johannesburg, 2021)
It is no secret that there has been an increase in international trade in recent decades. Natural and juristic persons have taken it upon themselves to trade both domestically and internationally. As international trade increases so too do the conclusion of international commercial contracts. When individuals enter into an international contract, one particularly important issue, and one that should be foremost in the minds of the contracting parties, is which legal system will govern their agreement? Therefore, a significant factor to any international commercial contract is whether the parties have the freedom to choose the law applicable to their agreement and to choose the court that will adjudicate upon their contractual disputes, and if so, to what extent may the parties exercise their freedom of choice?... LL.M. (International Commercial Law)
Keywords: Commercial policy; Commercial treaties; International trade

The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

An analysis of the consequences of a business rescue moratorium on legal proceedings on property owners - Ngubane, Samukelo Siyanda (University of KwaZulu-Natal, 2021)
It has been over a decade since the Companies Act 71 of 2008 introduced business rescue proceedings which provided for the rescue of financially distressed companies. This procedure replaced the then statutory procedure of judicial management under Companies Act 61 of 1973. The business rescue proceedings begin with the general moratorium or stay on legal proceedings against the company or its property. This has a consequence that any claims against the company may only be enforced with the consent of the business rescue practitioner or the leave of the court. However, the courts continue to grapple with the interpretation, effect, and application of the key elements of business rescue provisions while always striving to accord respect to the legislative intention of business rescue as set out in section 7(k) of the Companies Act 71 of 2008. After a decade since its introduction, it is an opportune time to ascertain whether the business rescue proceedings is an effective corporate rescue procedure suitable to the modern-day demands of the South African economy. The research analyses the effect and the consequences of the moratorium on the rights of property owners. The moratorium has the effect that companies are given temporary immunity to actions brought by creditors which would have been due and enforceable. In this regard, the property leased by the property owner remains occupied by the company during business rescue proceedings as the property owner is barred by the moratorium to institute legal proceedings against the company. Further, when the repossession of the property is not possible and the rental due or installment is not payable by the company, the business rescue proceedings encroaches on the right of the property owners. The purpose of the research is to highlight the effect of the moratorium on the lease agreement between the company and property owners and the possible protection of the property owners’ rights. The study includes a critical analysis of judicial decisions on the moratorium, together with a discussion of the legal position in comparable foreign jurisdictions. In my conclusion, based on the findings, the business rescue is not free from imperfection. Therefore, I recommended that the legislature amend some parts of Chapter 6 of the Companies Act 71 of 2008.
Keywords: Companies Act 71 of 2008; Corporate rescue procedure; Financially distressed companies; South Africa; Stay on legal proceedings

A Third World approach to the role of South Africa, Nigeria and Kenya in the multilateral trading system - Nzimande, Nosiphiwo (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: GATT; General Agreement on Trade and Tariffs; International Trade; Kenya; Nigeria; Regional Trade Agreements (RTAs); South Africa; WTO; World Trade Organization; World trade

Takeover and shareholders' agreements - Sabatini, Federico (LUISS Guido Carli, 2021)
The OPA. Notions of takeover bids. Recognising and distinguishing the various forms of control within a company. Type of takeover bid. Subsequent defence techniques. The US control market and details of M&A and tender offers. Bids and acquisitions in China. Comparative European case studies. Shaldeholders' agreements. Regulatory sources and definition of covenants. Concerted action. Takeover obligations arising from concerted action. Cases. The Fondiaria-Sai case. Unipol-BNL. Other case of exemption.